The TIP60 Complex Is a Conserved Coactivator of HIF1A - Joel I. Perez-Perri; Veronica L. Dengler; K. Audrey Audetat; Ahwan Pandey; Elizabeth A. Bonner; Marjeta Urh; Jacqui Mendez; Danette L. Daniels; Pablo Wappner; Matthew D. Galbraith; Joaquín M. Espinosa (Cell Reports, 2016)
Hypoxia-inducible factors (HIFs) are critical regulators of the cellular response to hypoxia. Despite their established roles in normal physiology and numerous pathologies, the molecular mechanisms by which they control gene expression remain poorly understood. We report here a conserved role for the TIP60 complex as a HIF1 transcriptional cofactor in Drosophila and human cells. TIP60 (KAT5) is required for HIF1-dependent gene expression in fly cells and embryos and colorectal cancer cells. HIF1A interacts with and recruits TIP60 to chromatin. TIP60 is dispensable for HIF1A association with its target genes but is required for HIF1A-dependent chromatin modification and RNA polymerase II activation in hypoxia. In human cells, global analysis of HIF1A-dependent gene activity reveals that most HIF1A targets require either TIP60, the CDK8-Mediator complex, or both as coactivators for full expression in hypoxia. Thus, HIF1A employs functionally diverse cofactors to regulate different subsets of genes within its transcriptional program.